Automated Elephant Entry Prevention for Human and Crop Protection - K, Mahalakshmi; Ramaiah G N, Kodanda; Kishore, Nandha; Ramesh, K. (International Journal of Engineering and Technology, 2018)
Farming in areas with elephants has been the norm in many parts of Asia for thousands of years. In particular, farmers have settled closer to areas where elephants are present and started growing crops. Elephant raids occur in the night time where people do not notice the presence of an elephant until it starts an oï¬€ensive behavior. Such raids damage the crops, harvest storages and homes in addition to causing deaths of humans. A multitude of traditional methods have been developed through the ages to reduce and prevent crop raiding by elephants like shouting, drum-beating, noise-making, use of fire crackers, electric fencing, lights and torches. Such activities may also indicate to elephants that their presence is detected, and that they have to contend with aggressive humans. In the proposed system,Â Â  automated detection of the presence of elephant is done by analyzing the infrasonic sounds produced by elephants and they are prevented from entering into farms by propagating the offensive sounds in low frequencies without human intervention.Â